Manajemen Perubahan Melalui Perencanaan Proyek: Strategi Pengendalian Efektif di Lembaga Pendidikan - Refnawati, Refnawati; Yovica, Alia; Octavia, Lidya Fransiska; Fazis, M. (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to understand change management through project planning as an effective control strategy in educational institutions. This study uses a literature review approach as the main method. Data sources are obtained from various scholarly articles, academic books, proceedings, and policy documents. The databases used include Google Scholar, with search keywords such as